2017
DOI: 10.2118/185953-pa
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility and Rheology of High-pH Borate Gels Prepared With Produced Water for Hydraulic-Fracturing Applications

Abstract: Summary Fracturing fluids are commonly formulated with pond water to ensure reliable rheology. However, pond water is becoming more costly, and in some areas, it is difficult to obtain. The use of produced water in hydraulic fracturing has gained increased attention in the last few years, because it could solve freshwater-acquisition difficulties and reduce disposal costs. A major challenge, however, is its high content of total dissolved solids (TDSs), which could cause formation damage and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Effect of (left) HEDTA and (right) GLDA concentrations on the tolerance to both Ca and Mg ions. This figure was reproduced with permission from ref . Copyright 2018 Society of Petroleum Engineers.…”
Section: Chelating Agents As Hydraulic Fracturing Fluid Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of (left) HEDTA and (right) GLDA concentrations on the tolerance to both Ca and Mg ions. This figure was reproduced with permission from ref . Copyright 2018 Society of Petroleum Engineers.…”
Section: Chelating Agents As Hydraulic Fracturing Fluid Additivesmentioning
confidence: 99%
“…Elsarawy et al 159 expanded the study by adding the impact of common mono-and divalent ions on the viscosity and precipitation of a borate cross-linked polymer mixed with synthetic seawater. The study showed that, by adding 1 wt % HEDTA, the fluid system increased its tolerance (before precipitation) to Ca and Mg ions to 1000 and 100 ppm from an initial tolerance of 400 and 25 ppm, respectively.…”
Section: Chelating Agents As Hydraulic Fracturingmentioning
confidence: 99%
“…Laboratory studies and simulations show that carbonate scale is favored when aqueous Ca 2+ or Fe 2+ ions combine with aqueous CO 3 2– ions under elevated pH and low-pressure conditions . Brucite scaling is less common but does materialize if Mg-based dissolvable tools or cross-linked gels are used at conditions (e.g., pH 12 and [Mg 2+ ] of >25 ppm) favoring brucite as a degradation product. , A common formulation for dissolving carbonate scale includes adding corrosion-inhibited 15% HCl acid formulated with EDTA or citrate chelating agents for capturing the divalent cations and an ethoxylated alcohol surfactant.…”
Section: Scale Inhibitorsmentioning
confidence: 99%
“…Two types of ions are abundant in SW: divalent (Ca, Mg) and monovalent (Na, K) ions; these ions affect the fracturing fluid rheology and could damage the formation. The monovalent ions only affect the rheology when divalent ions are absent [ 35 ]. At a pH greater than 10, we can expect the precipitation of Ca and Mg ions, forming different scales.…”
Section: Introductionmentioning
confidence: 99%